Multivariate spatial conditional extremes for extreme ocean environments. (1st March 2022) - Shooter, Rob; Ross, Emma; Ribal, Agustinus; Young, Ian R.; Jonathan, Philip
Abstract: The joint extremal spatial dependence of wind speed and significant wave height in the North East Atlantic is quantified using Metop satellite scatterometer and hindcast observations for the period 2007–2018, and a multivariate spatial conditional extremes (MSCE) model, ultimately motivated by the work of Heffernan and Tawn (2004). The analysis involves (a) registering individual satellite swaths and corresponding hindcast data onto a template transect (running approximately north-east to south-west, between the British Isles and Iceland), (b) non-stationary directional-seasonal marginal extreme value analysis at a set of registration locations on the transect, (c) transformation from physical to standard Laplace scale using the fitted marginal model, (d) estimation of the MSCE model on the set of registration locations, and assessment of quality of model fit. A joint model is estimated for three spatial quantities: Metop wind speed, hindcast wind speed and hindcast significant wave height. Results suggest that, when conditioning on extreme Metop wind speed, extremal spatial dependence for all three quantities decays over approximately 600–800 km. Highlights: Characterise joint extremal spatial dependence between multiple metocean variables. Methodology motivated by model of Heffernan and Tawn (2004). Satellite scatterometer (Metop) and hindcast data (Reistad et al., 2011) incorporated. Marginal directional and seasonal covariate effects accommodated. Extremal spatial dependence decays over 600–800 km for conditioning on an extreme occurrence of wind speed.